Alteration of Pulmonary Artery Integrin Levels in Chronic Hypoxia and Monocrotaline-Induced Pulmonary Hypertension - Umesh, Anita (S. Karger AG, 2011)
BACKGROUND: Pulmonary hypertension is associated with vascular remodeling and increased extracellular matrix (ECM) deposition. While the contribution of ECM in vascular remodeling is well documented, the roles played by their receptors, integrins, in pulmonary hypertension have received little attention. Here we characterized the changes of integrin expression in endothelium-denuded pulmonary arteries (PAs) and aorta of chronic hypoxia as well as monocrotaline-treated rats. METHODS AND RESULTS: Immunoblot showed increased α(1)-, α(8)- and α(v)-integrins, and decreased α(5)-integrin levels in PAs of both models. β(1)- and β(3)-integrins were reduced in PAs of chronic hypoxia and monocrotaline-treated rats, respectively. Integrin expression in aorta was minimally affected. Differential expression of α(1)- and α(5)-integrins induced by chronic hypoxia was further examined. Immunostaining showed that they were expressed on the surface of PA smooth muscle cells (PASMCs), and their distribution was unaltered by chronic hypoxia. Phosphorylation of focal adhesion kinase was augmented in PAs of chronic hypoxia rats, and in chronic hypoxia PASMCs cultured on the α(1)-ligand collagen IV. Moreover, α(1)-integrin binding hexapeptide GRGDTP elicited an enhanced Ca(2+) response, whereas the response to α(5)-integrin binding peptide GRGDNP was reduced in CH-PASMCs. CONCLUSION: Integrins in PASMCs are differentially regulated in pulmonary hypertension, and the dynamic integrin-ECM interactions may contribute to the vascular remodeling accompanying disease progression.